Corporate Social Responsibility Disclosure, Tax Avoidance, and the Moderating Role of CEO Overconfidence in Indonesia - Dwi Nuryanti Kharisma Putri; Susi Sarumpaet (International Journal of Economics and Management Sciences, 2026)
This study examines the relationship between Corporate Social Responsibility (CSR) disclosure and tax avoidance, with CEO Overconfidence considered as a moderating factor. The research focuses on non-cyclical consumer goods companies listed on the Indonesia Stock Exchange during the 2022-2024 period. Using annual and sustainability reports, the analysis employs multiple linear regression and moderated regression analysis (MRA). Robust standard errors based on the Newey-West method are applied to ensure reliable estimation. The results indicate that CSR disclosure does not have a significant direct effect on tax avoidance. However, CEO Overconfidence significantly moderates the relationship between CSR disclosure and tax avoidance, highlighting the role of executive behavioral characteristics in corporate tax decisions. These findings suggest that CSR disclosure alone is insufficient to explain firms’ tax avoidance behavior without considering managerial traits. The study contributes to the literature by integrating behavioral perspectives into tax avoidance research and emphasizing the importance of executive oversight in aligning CSR practices with responsible tax behavior.